THE SYNERGISTIC ROLE OF BIOCHAR AND PLANT GROWTH-PROMOTING RHIZOBACTERIA IN MANAGING ENVIRONMENTAL STRESS IN FIELD CROPS: A REVIEW - A. A. H. Salata; G. G. Borisova; M. G. Maleva (مجلة الأنبار للعلوم الزراعية)
The world climate is undergoing significant changes due to the extensive release of greenhouse gases. These emissions lead to environmental challenges such as drought, salinity, and heavy metal contamination which have a long-lasting impact on food security, particularly in developing countries. This requires identifying ecologically sustainable and economically efficient methods to tackle these environmental stresses. Biochar has many distinctive attributes that enhance its efficacy, cost-effectiveness, and ecological compatibility. They include its ability to improve soil health, promote crop growth and production, and regulate nutrient dynamics via features that maintain microbial life. Biochar has a substantial amount of organic carbon, is rich in nutrients like nitrogen (N), phosphorus (P), and potassium (K), exhibits a high degree of porosity, and demonstrates a remarkable ability to retain water. Plant growth-promoting rhizobacteria (PGPR) function as a co-evolutionary process between plants and microbes, displaying both antagonistic and synergistic interactions with microorganisms and soil. This review emphasizes the significance of synergistically using biochar and PGPR to enhance soil quality and agricultural production in both optimal and challenging environments, provided they are mutually beneficial. The implementation of this approach enhances the effectiveness of resource conservation, alleviates both biotic and abiotic stresses, and ultimately mitigates the impacts of climate change